ANALISIS TERMAL SIKLUS RANKINE ORGANIK PADA PEMBANGKIT LISTRIK TENAGA PANAS BUMI - Fathoni, Rachmat
Indonesia has the potential geothermal power of 28,170 MW or about 40% of world’s geothermal potency. Until 2009, only 1,189 MW were installed all over the country. The government has projected by 2025, there are 9,466 MW new power plant mounted through all over the country. This final project reported the utilization of Organic Rankine Cycle (ORC) in Geothermal Power Plant in two locations, South Sumatera and North Sulawesi. The simulation itself, using a software called HYSYS 7.3. There are three systems being analyzed in this final project, namely Binary Power Plant, Condensing Steam Turbine and Brine Binary Power Plant Bottom Cycle, and Backpressure Steam and Binary Power Plant in Combined Cycle. Working fluid used in this cycle is R-134a (1,1,1,2- tetrafluoroethane). Obtained from the results of the study that in South Sumatera Power Plant for first system produces net power 7,656.4 kW with exergetic efficiency 30.8%, thermal efficiency 11.7%. Second system produces 19,636.73 kW with ORC addition 5,149 kW, exergetic efficiency 78.9%, thermal efficiency 30.08% and third system produces 18,977.3 kW with ORC addition 11,030 kW, exergetic efficiency 76.3% and thermal efficiency 29.7%. While in the North Sulawesi Power Plant, first system produces net power 7,651.8 kW, with exergetic efficiency 16.2%, thermal efficiency 6.5%. Second system produces 28,363.73 kW with ORC addition 11,310 kW, with exergetic efficiency 60.36% and thermal efficiency 24%. And last system produces 22,076.6 kW with ORC addition 11,850 kW with exergetic efficiency 46.98% and thermal efficiency 18.73%. From the result of the study, the system that produces the highest power is Condensing Steam Turbine and Brine Binary Power Plant in Bottom Cycle.